Pengaruh Kecepatan Pelayanan dan Disiplin Kerja terhadap Kepuasan Nasabah Bank Syariah Indonesia di Kabupaten Batang Hari - Niki Kosasih; Sumantri Sumantri; Hakiki Rizkianda (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study investigates the influence of service speed and work discipline on customer satisfaction in Sharia banking. Using a quantitative approach with multiple linear regression, data were collected from 100 customers of Bank Syariah Indonesia (BSI) in Batang Hari. Findings reveal that both service speed and work discipline have significant positive effects on customer satisfaction. This study contributes to the growing literature on Islamic banking service quality by integrating recent perspectives on digital self-service technology and employee discipline, suggesting managerial implications for enhancing customer satisfaction in the era of digital banking.